On the prediction of tip vortices in the near wake of the MEXICO rotor using the actuator surface method. (1st January 2012) - Breton, Simon-Philippe; Watters, Christophe Sibuet; Masson, Christian; Gomez-Iradi, Sugoi; Munduate, Xabier
The rotor of the model experiments under controlled conditions (MEXICO) wind turbine is modelled using the actuator surface (AS) method, wherein the blades are represented by singular surfaces of velocity and pressure discontinuities. A 3D control-volume finite-element method (CVFEM) is used to solve the Navier-Stokes equations, with appropriate adaptations to incorporate the AS action on the flow. The ability of the AS method to correctly model vorticity evolution and conservation in the wake of the MEXICO rotor is investigated. Experimental data in the form of PIV measurements collected from wind tunnel tests, as well as full CFD computations, are used for comparison purposes. This study is done in terms of the position, size, and strength of the vortices, which are determined using three analytical methods whose results are compared and discussed. Comparison with experimental results will help in determining how realistic the predictions from the AS model are, while comparison with full CFD computations will allow to shed light on the pros and cons of the AS method in comparison with full CFD computations.